Study, Design and Development of an AC-DC Buck+Boost Converter Applied to Battery Chargers for Electric Vehicle - Francisco JosÃ Barbosa de Brito JÃnior (2013)
This work presents a study and design of an electronic power converter topology for on-board application in a battery charger for plug-in electric vehicles. The proposed topology is based on AC-DC converter Buck+Boost, which one is very attractive for this application due to its buck and boost characteristics in a single-stage power processing. Furthermore, this topology presents reduced weight and volume, since there is no transformer and only few components are presented in its structure. A theoretical study is performed through of qualitative and quantitative analysis, besides it is investigated the switching process and losses in the converter components. It is also performed a design example of a battery charger with rated output power of 1 kW, input voltage 220 Vac RMS and output voltage of 162 Vdc, corresponding to 12 batteries connected in series. A prototype for the indicated specifications was constructed in laboratory and tested experimentally. The simulation and experimental results obtained are used to validate the theoretical analysis and design. For rated load, it was obtained an efficiency of 96.5% and a power factor of 0.992, thus showing the effectiveness of the proposed converter.